Protective Effect of Anthocyanin-Enriched Polyphenols from Hibiscus syriacus L. (Malvaceae) against Ultraviolet B-Induced Damage - Wisurumuni Arachchilage Hasitha Maduranga Karunarathne; Ilandarage Menu Neelaka Molagoda; Kyoung Tae Lee; Yung Hyun Choi; Sang-Mi Yu; Chang-Hee Kang; Gi-Young Kim (MDPI AG, 2021)
Anthocyanin-enriched polyphenols from the flower petals of H. syriacus L. (Malvaceae, AHs) possess anti-septic shock, anti-oxidant, and anti-melanogenic properties. However, whether AHs positively or negatively regulate ultraviolet B (UVB)-mediated photoaging and photodamage remains unclear. This study aims to investigate the protective effect of AHs against UVB-induced damage. We examined the photoprotective effects of AHs on UVB-induced apoptosis, endoplasmic reticulum (ER) stress, and mitochondrial reactive oxygen species (mtROS). AHs prevented UVB irradiation-induced apoptosis of HaCaT keratinocytes by inhibiting caspase activation and ROS production. Moreover, AHs restored the survival rate and the hatchability of UVB-irradiated zebrafish larvae without any abnormalities. Furthermore, AHs inhibited UVB-induced ER stress, resulting in a decrease in mtROS production via the stabilization of the mitochondrial membrane potential. Our results indicate that AHs inhibit UVB-induced apoptosis by downregulating total cytosolic ROof cytosolic CaS and ER-mediated mitoROS production in both HaCaT keratinocytes and zebrafish larvae. These findings provide evidence for the applications of AHs to protect skin from UVB-induced photodamage.